Pengaruh Struktur Modal, Suku Bunga Dan Piutang Terhadap Profitabilitas Pada Perusahaan Perbankan Yang Terdaftar Dibursa Efek Ind0nesia Periode 2019 – 2021 - Agnolita Sitanggang; Michael Aldo Saputra Sibarani; Mohd Nawi Purba; M Ikbar Pratama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to find out how the effect of Capital Structure, Interest Rates, and Receivables on Profitability in Banking companies on the Indonesia Stock Exchange in the period of 2019 - 2021. This research uses a quantitative approach method with this type of descriptive research. The independent variables in this study are profitability and the dependent variables are capital structure, interest rates and receivables. Sample data collection used purposive sampling method with the help of SPSS software to carry out statistical analysis tests. The results showed that simultaneously capital structure, interest rates, receivables have a significant effect on profitability. while partially capital structure, interest rates have a significant negative effect on profitability but the receivables variable has a positive and significant effect on profitability. Keywords: SM, SB, Receivable and ROA